Divergent territories- local education policies in the face of territorial and educational inequalities - Sebastião, João; Gonçalves, E. (XV Congreso Español de Sociología - Sociología para la sociedad digital, 2024)
Divergent territories: local education policies in the face of territorial and educational inequalities João Sebastião, joao.sebastiao@iscte-iul.pt, CIES – Iscte. Eva Gonçalves, eva_patricia_goncalves@iscte-iul.pt, CIES – Iscte. Introduction This paper aims to analyse how socio-spatial segregation mechanisms contribute to the reproduction of social inequalities in education, and how municipal education policies address this issue. The existence of socio-spatial segregation mechanisms has been a central element in the organisation of the territory, particularly in a context of globalisation and the circulation of capital. One of the most important features of this process concerns the growing divergence between the metropolises and the places left behind (Kemeny and Storper, 2020: 3), a process resulting from the largest cities continuing to attract population and economic activity to the detriment of peripheral and rural regions in a vicious cycle of segregation (Tammaru et al, 2021). The concentration of wealth in certain regions makes the more fragile ones highly susceptible to global trends (Manduca, 2019), an example of which is the different exposure to climate change. One of the consequences of this process of neoliberal reconfiguration of space and the populations that inhabit it concerns the division of populations into progressively more socially homogenous areas and, as a consequence, the production of school populations that are themselves segregated (Sebastião, 2009). This topic is particularly relevant today in Portugal, as the education system is undergoing a process of reconfiguration with the transfer of competences and services from the government to municipalities and school groups, creating new areas of autonomy (Martins, Capucha and Sebastião, 2019). This is a structural change, since historically there has been a strongly centralised matrix, independent of regional or local communities, with a strong relationship between social origin and successful school trajectories (Sebastião, 2009, Mata, 2015, Abrantes, 2020). From 2022 onwards, the Intermunicipal Communities and Municipal Councils began to develop their own educational policies within the scope of the new educational competences, with the main strategic planning mechanisms being the Regional Strategic Educational Plans and the Municipal Educational Charters. Theoretical and methodological planning The collaboration of a team of sociologists in the preparation of this plans in two territories made it possible to analyse the territorial, social and cultural dynamics and reflect on their educational development strategies. We analysed a municipality in the Lisbon Metropolitan Area and a group of municipalities located in a rural area in the south of Portugal that are part of the same Intermunicipal Community (same district). The decision to make this choice is the result of the team's reflection on territorial dynamics and their relationship with the profound educational inequalities identified between these territories. To this end, we mobilised the information compiled in these two projects using a mixed approach designed to triangulate information, using questionnaires applied to a representative sample of teachers in each territory, semi-directive interviews applied to the education councillors of the municipal councils and the heads of schools in the public and private professional network, and focus groups with pupils, parents and various community entities as part of the consultation with local stakeholders; collecting and analysing strategic documents from the school groups and municipalities and socio-economic, demographic and educational statistical data from the two territories. This information was supplemented with field notes recorded by the researchers. All the consultation instruments were tested beforehand and the conclusions were validated during the sessions to present and discuss the documents with the respective communities. The interviews were transcribed in full and then subjected, along with the strategic documents, to content analysis using maxqda (version 2020); and the statistical data, those collected from national, regional or municipal databases and those constructed using the questionnaire, were analysed using SPSS (version 27), both types of analysis complying with the methodological recommendations commonly recognised by the scientific community (Bryman, 2012; Creswell, 2014; Marying, 2000). Results The first territory, located in the Lisbon Metropolitan Area, is undergoing an accelerated process of gentrification, mostly attracting a highly qualified cosmopolitan population with high purchasing power, being the municipality with the highest average individual income rate in Portugal (GPEARI, 2024). Internally, it is characterised by urban dynamics marked by housing and social segregation, resulting from the progressive appropriation of land for housing for people with high purchasing power and the pushing of people with low purchasing power to peripheral areas within and outside the municipality, resulting in progressively homogeneous and socially differentiated urban areas. From an educational point of view, it is characterised by internal educational asymmetries, with school population and educational offerings that are very different between the most valued areas on the coast and the most deprived areas in the interior of the municipality. In this municipality, the existing cultural diversity is seen as an advantage in the context of a globalised, digitally-focused municipal economy, which is mostly highly qualified. As a municipality with high resources, it seeks to develop a network of schools characterised by excellence and technological innovation, as the transition to emergency remote education during the pandemic has shown, with no significant obstacles, both in terms of equipment and educational support. The local education authorities realise that the educational inequalities within the municipality can be a disadvantage, both symbolically and in terms of human resources, for the overall economic transformation objectives pursued by the municipality, so they have defined a proactive strategy aimed at responding to a diverse educational demand within a dense social and productive territory. They are therefore seeking to implement a number of actions to reduce tracking situations in the most privileged areas, inequalities in educational success between school groups and to develop a more diverse educational offer than the existing one, which is highly concentrated on STEM. The second set of municipalities, rural in nature, with increasingly industrialised and automated agricultural activity, although large in territorial size, is marked by strong demographic desertification and ageing, with a low-skilled population and much lower purchasing power than the first municipality. Here, the presence of immigrants is socially "invisible", essentially ensuring the different needs of low-skilled labour, and is viewed with suspicion and poor recognition by local institutions. From an educational point of view, we find a sparse network of schools, faced with the constant threat of school closures, with relative educational homogeneity, characterised by average school results, although generally higher than expected due to the prevailing socio-economic contexts. This network of municipalities is characterised by weak financial and human resources in the area of education, and there have been many asymmetries in access to education during the pandemic, whether due to the lack of technological resources, poor digital communications or the difficulty in guaranteeing effective support for all students. From the point of view of local education policies, the urgency of not losing more students emerges as central to a "damage control" strategy, in which education is considered an instrument of survival of the rural hinterland. Educational challenges are tackled in isolation by each municipality, with difficulty in promoting co-operation between school groups, vocational schools and municipalities more widely. Little importance is given to the challenges resulting from the growth in the number of immigrants in the territory, which appear almost invisible in the interviewees' speeches. The two territories face very different challenges as a result of the neoliberal restructuring of the territory, reflected in the concentration of capital in the most central areas of the metropolises and the progressive devaluation of peripheral and rural areas. The information analysed confirms that this process has a significant impact on educational opportunities in the two territories, with marked differences in the diversity of educational offers, the quality of equipment and educational support mechanisms. This difference is accentuated by the fact that the urban area has a high capacity to attract favoured social classes, an attraction promoted by the municipality's urban and economic strategy. This strategy results in the expulsion of the less favoured population to other areas of the metropolis and the transformation of the school population, which becomes progressively more socially homogeneous. The opposite is true in rural municipalities, where attending school is often synonymous with outward mobility, especially at the higher levels of the education system, thus exacerbating the negative demographic dynamic. Schools are isolated in a vast territory, with few contacts and poor means of mobility, and often with educational projects that compete with each other. Those who end up staying often have low expectations of the usefulness of attending school, since the technological modernisation of agriculture means automation processes and a reduction in the use of low-skilled labour. Cuestiones de partida ¿Cómo contribuyen los mecanismos de segregación socioespacial a la reproducción de las desigualdades sociales en la educación? ¿Cómo lo abordan las políticas educativas municipales? Dos territorios contrastados T1  T 1 (un municipio urbano AML)  Costero  Gentrificado  Fuerte crecimiento urbano  Población altamente cualificada  Alto poder adquisitivo  Economía de alta tecnología  Fuertes asimetrías educativas internas  Municipio con elevados recursos  Presión para construir escuelas modernas  La diversidad cultural se considera un recurso  T 1 - El objetivo político municipal: "Queremos tener los mejores estudiantes del país“  Estrategia proactiva que pretende construir un futuro capaz de dar respuesta a una demanda educativa elevada y diversa dentro de un territorio social y productivamente denso  Acciones para reducir el tracking y las desigualdades en el éxito educativo entre grupos escolares  Una oferta educativa más diversa que la actual, muy concentrada en materias STEM  Foco en la transición digital Dos territorios contrastados T2  T 2 (13 municipios interior rural)  Demografía poco densa, muy envejecida  Repulsión demográfica/desertificación  Población poco cualificada  Bajo poder adquisitivo  Economía basada en la agricultura industrial  Relativa homogeneidad educativa  Municipios con escasos recursos  Presión financiera para cerrar escuelas  ‘Escaso’ reconocimiento de la diversidad cultural: racismo o invisibilidad.  T 2 - El objetivo político municipal : "No podemos permitirnos perder más alumnos...“  Una estrategia de "control de daños" en la que la educación se considera un instrumento de supervivencia en el interior rural  Dificultad de planificación en términos de un territorio más amplio que el coordinado por cada municipio  Competición para atraer estudiantes por parte de centros escolares, centros de formación profesional y municipios.  Dificultad en promover la cooperación para acceder a los recursos digitales  Incapacidad estratégica de abordar la diversidad cultural En resumen, Podemos concluir que existe una fuerte relación entre  Reestructuración neoliberal del territorio:  Concentración del capital en las zonas más céntricas de las metrópolis  Atracción de las clases sociales favorecidas a eses territorios  Expulsión de la población menos favorecida a otras zonas de la metrópolis  Devaluación progresiva de las zonas periféricas y rurales  Desinversión / fuga de capitales  Desertificación rural / descalificación de las periferias urbanas  Oportunidades educativas en los dos territorios:  Transformación de la población escolar, que se vuelve progresivamente más homogénea socialmente  Diferencias efectivas en la diversidad de las ofertas educativas / desigualdad de oportunidades educativas  Diferencia significativa en el acceso a los recursos: material didáctico, tecnológicos  Grandes diferencias en las redes de apoyo educativo a los niños con discapacidad o dificultades de aprendizaje.  Escasa contribución de la escuela a la cohesión territorial. Abrantes, Pedro (2022). Educação e classes sociais em Portugal: continuidades e mutações no século XXI. Sociologia, Problemas e Práticas, 99, 9-27. Bryman, A. (2012). Social research methods.4th Edition. New York: Oxford University Press. GPEARI (2024). Fiscalidade e Desigualdade. https://www.gpeari.gov.pt/web/pt/fiscalidade-e-desigualdade Creswell, J. W. (2014). Research Design. Qualitatative, Quantitative, and Mixed Methods Approaches. 4th Edition. Thousand Oaks: Sage Publications. Kemeny, Tom and Storper, Michael (2020). Superstar Cities and Left-Behind Places: Disruptive Innovation, Labor Demand, and Interregional Inequality. LSE-International Inequalities Institute, Working paper 41. Martins, Susana da Cruz, Capucha, Luís and Sebastião, João (orgs.) (2019) School autonomy, organization and performance in Europe – A comparative analysis for the period from 2000 to 2015. Cies-IUL/Smashwords, Lisboa. ISBN: 978-972-8048-46-4. Manduca, Robert A (2019). The Contribution of National Income Inequality to Regional Economic Divergence. Social Forces, 98 (2): 622-648, doi:10.1093/sf/soz013 Mayring, P. (2000). Qualitative Content Analysis. Forum Qualitative Sozialforschung Forum: Qualitative Social Research, 1(2). https://doi.org/10.17169/fqs-1.2.1089 Mata, João T. (2015). A igualdade e a desigualdade na educação em Portugal [Tese de doutoramento, Iscte - Instituto Universitário de Lisboa]. Repositório do Iscte. http://hdl.handle.net/10071/12469 Nunes, Luís Catela (Coord.), Carneiro, P., Freitas, P., Nunes, M. E., Chaves, A., Cal, S. (2023). Da desigualdade social à desigualdade escolar nos municípios de Portugal. Porto, Fundação Belmiro de Azevedo Sebastião, João (2009) Democratização do ensino, desigualdades sociais e trajectórias escolares, Lisboa, Fundação Calouste Gulbenkian, ISBN 978-972-31-1286-3. Tammaru, T., Knapp, D., Silm, S., van Ham, M., & Witlox, F. (2021). Spatial Underpinnings of Social Inequalities: A Vicious Circles of Segregation Approach. Social Inclusion, 9(2), 65-76. doi:https://doi.org/10.17645/si.v9i2.4345